(untitled) (Global Journal of Management and Business Research, 2018)
This paper analysis the impact of prudential regulation on banking risk using the measurement technique "z-score" by introducing the financial and economic determinants (real GDP growth rate, inflation, real GDP growth rate, inflation, the governance indicator, etc.). For this reason, we used a sample of 146 conventional banks in the MENA region during the 2003-2014 period, whose purpose was to determine the specificities of these countries about the determinants of banking risk.